2010
DOI: 10.1021/ic902406h
|View full text |Cite
|
Sign up to set email alerts
|

Uranyl Complexes of Carboxyl-Functionalized Ionic Liquids

Abstract: Uranium(VI) oxide has been dissolved in three different ionic liquids functionalized with a carboxyl group: betainium bis[(trifluoromethyl)sulfonyl]imide, 1-(carboxymethyl)-3-methylimidazolium bis[(trifluoromethyl)sulfonyl]imide, and N-(carboxymethyl)-N-methylpyrrolidinium bis[(trifluoromethyl)sulfonyl]imide. The dissolution process results in the formation of uranyl complexes with zwitterionic carboxylate ligands and bis[(trifluoromethyl)sulfonyl]imide (bistriflimide) counterions. An X-ray diffraction study o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
73
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(75 citation statements)
references
References 43 publications
2
73
0
Order By: Relevance
“…12,33 Formation of uranyl speciations (coordinated anions) in such IL systems appeared to be controlled. The results from experiments 26,40,41 and calculations 42,43 (6), 3TT, and 3TG, as observed in interionic interactions, are discussed in relation to the different cations and temperatures. Additionally, novel transformations were observed with multiple characterizations of compounds 2, 3TT, 3TG, and 6.…”
Section: ■ Introductionmentioning
confidence: 91%
“…12,33 Formation of uranyl speciations (coordinated anions) in such IL systems appeared to be controlled. The results from experiments 26,40,41 and calculations 42,43 (6), 3TT, and 3TG, as observed in interionic interactions, are discussed in relation to the different cations and temperatures. Additionally, novel transformations were observed with multiple characterizations of compounds 2, 3TT, 3TG, and 6.…”
Section: ■ Introductionmentioning
confidence: 91%
“…Recently, Binnemans and coworkers have reported that the betainium bis(trifluoromethylsulfonyl)imide ([Hbet][Tf 2 N], [Hbet] + = (H 3 C) 3 N + CH 2 COOH, [Tf 2 N] À = (CF 3 SO 2 ) 2 N À , see Scheme 1) has a selective solubilizing ability for metal oxides such as Sc 2 O 3 , Y 2 O 3 , Ln 2 O 3 (Ln = La, Nd, Sm, Eu, Gd, Dy, Ho, Er, Tm, Yb, Lu), UO 3 , ZnO, and its binary mixture with water forms a homogeneous phase at P 328 K, so-called an upper critical solution temperature (UCST) [21][22][23][24][25][26][27][28][29][30][31][32]. Thus, raising temperature above UCST does not only promote chemical reactions like complexation of M n+ with an extractant, but also give an additional benefit to homogenize the biphasic system.…”
Section: Introductionmentioning
confidence: 99%
“…Some recent reports have involved task-specific ionic liquid (TSILs) that have potential applications in metal extraction. [24][25][26][27][28][29][30][31][32][33][34][35] TSILs appended with some functional groups that could impart particular reactivity, thereby enhancing their capacity for interaction with metal ions are an interesting option. This approach that does not require the addition of extra extracting agent would effectively solve the problem of miscibility between the extracting agent and solvent.…”
Section: Introductionmentioning
confidence: 99%